Penerapan Keamanan Owasp Terhadap Aplikasi GTFW Pada Website Universitas Battuta - Baginda Harahap (Indonesian Scientific Journal, 2021)
In this study, we will test the penetration of GTFW-based applications that have been carried out, then obtain the results as a session management category vulnerability test, namely 3 that did not pass, namely cookie attributes, CSRF, and session timeout, then the vulnerability of the input validation category there was 1 that did not pass, namely stored XSS. The xplorin application has a cookie attribute vulnerability with a Medium vulnerability risk level. The xplorin application has a CSRF vulnerability with a Medium vulnerability risk level. The xplorin application has a session timeout vulnerability with a Low vulnerability risk level. The xplorin application has a stored XSS vulnerability with a Low risk level of vulnerability.